Comparison between SAW and WASPAS Methods in Determining the Location of the Transit Warehouse of PT. TG - Frainskoy Rio Naibaho (Universitas Medan Area, 2021)
This study aims to determine the location of the transit warehouse of PT. TG. For reasons of corporate strategy, so that PT. TG conducted a search for warehouse transit locations by considering five factors. The five factors are population density, distance from the head office, ease of access to the location, land price factors, and social environmental factors. The search for the location of the transit warehouse was carried out precisely to support the progress of the company. The five criteria are grouped into two types, namely benefits and costs. Management of PT. TG provides six alternative warehouse transit locations. Selection of location for the transit warehouse of PT. TG is important because the warehouse is an important facility in a company. The warehouse has an important role in ensuring the supply chain for inventory goods. The method used is the Simple Additive Weight method and the Weight Aggregated Sum Product Assessment method. The results of the weight calculation against the criteria produce an option that can help the management of PT. TG in making the decision for the location of the transit warehouse. One of the six alternatives will be selected based on the value of the largest V or Q calculation. The results of the processing of the SAW method and the WASPAS method show that Sunggal Subdistrict is the best location, with results V = 0.773 and Q = 0.746.